Escaping poverty traps? Collective action and property rights in postwar rural Cambodia - Weingart, Anne; Kirk, Michael (University of Pennsylvania Press, 2011)
The objective of the case study reported in this chapter was to identify effective practices and policy interventions at a local level that enhance the way in which cooperation or collective action and property rights have been used and shaped to build up secure assets and income streams for the rural poor in Cambodia. In order to provide policymakers, community groups, civil society organizations, and researchers with a better understanding of the property regimes in place, we assess existing property rights systems in rural Cambodia to identify what benefit streams poor people can rely on for their livelihood. We identify existing forms and mechanisms of economic and social cooperation, how they influence property rights systems, and to what extent the rural poor are part of village networks that contribute to resource protection. Based on this assessment, concrete linkages and feedback mechanisms among property rights, collective action, and poverty are analyzed at a village level. In concrete terms, we show what (common) resources poor households can use, what property rights systems govern these resources, and whether collective action, which is re-emerging after the genocide, helps poor people to address their needs. From these findings some policy implications can be drawn.